Effect of Propolis Application in Root Canal Therapy for Decontamination; Reversible or Irreversible Coronal Discoloration? - Zohreh Ahangari; mandana Naseri; Samin Banihashem; Sara Namjou; Leila Eftekhar (Mashhad University of Medical Sciences, 2021)
Introduction: Propolis is a resinous substance produced by honeybees. Despite antimicrobial properties, tooth discoloration has been reported during its application as intracanal medicament. The aim of this study was to assess the effect of intracanal propolis removal on crown discoloration. Methods: In this experimental study, after access cavity and canal preparation was performed in 40 intact anterior teeth, they were divided into three groups. In group 1 propolis was placed in the canal and pulp chamber while in group 2, it was applied into the canal only. The canals of third group were filled with distilled water as control. After six months, labial surfaces of all teeth were digitally photographed by a digital camera. Propolis was then completely removed and photography was repeated. Tooth color was evaluated in the labial surface using CIE Lab system and Photoshop software. Results: Overall color change (ΔE), change in lightness (ΔL), greenness-redness (Δa) and blueness-yellowness (Δb) were analyzed. ΔL and Δa values were significantly different in all three groups (p <0.001). The difference between groups 1 and 2 was not significant for ΔL or Δa, but groups 1 and 3 were significantly different in ΔL and Δa (p <0.001). Groups 2 and 3 were significantly different in ΔL and Δa (p <0.001). Conclusion: Coronal discoloration after six-month application of propolis as intracanal medicament was not reversed by its removal. Location of application of propolis (in the canal or both canal and pulp chamber) had no significant effect on degree of coronal discoloration.